Interplay of PNPLA3 and HSD17B13 Variants in Modulating the Risk of Hepatocellular Carcinoma among Hepatitis C Patients - Carla De Benedittis; Mattia Bellan; Martina Crevola; Elena Boin; Matteo Nazzareno Barbaglia; Venkata Ramana Mallela; Paolo Ravanini; Elisa Ceriani; Stefano Fangazio; Pier Paolo Sainaghi; Michela Emma Burlone; Rosalba Minisini; et al. (Gastroenterology Research and Practice)
A single-nucleotide polymorphism causing a C to G change in the PNPLA3 gene (rs738409) is associated with disease severity and development of hepatocellular carcinoma (HCC) in nonalcoholic fatty liver disease; the insertion variant rs72613567:TA of the 17β-hydroxysteroid dehydrogenase type 13 (HSD17B13) mitigates this detrimental effect. Our aim was to evaluate if the same holds true in chronic hepatitis C virus infection (HCV). With a case control retrospective study design, we selected 110 patients who developed HCC on a background of HCV infection, matching each patient for sex and age (±30 months) to three HCV-infected, non-HCC patients. All participants underwent genotyping for PNPLA3 and HSD17B13 gene variants. Both univariate and multivariate analyses of risk factors for advanced disease and HCC were performed. Carriage of PNPLA3 G∗ allele was associated with a trend of progressively more severe liver disease, from mild fibrosis to significant fibrosis, cirrhosis, and HCC (p=0.007). When the HSD17B13:TA status of these patients was taken into account, the abovementioned trend was strengthened among HSD17B13 major allele homozygotes and completely blunted among carriers of the minor allele (p=0.0003 and 0.953, respectively). In a conditional logistic regression model including diabetes and AST to platelet ratio index among predictor variables, the unfavourable genetic profile characterized by the coexistence of the PNPLA3 minor allele and HSD17B13 major allele (vs. all other possible combinations) was an independent risk factor for HCC (OR=2.00, 95% CI: 1.23-3.26) together with a history of alcohol abuse. In conclusion, carriage of the combination PNPLA3 minor allele and HSD17B13 major allele may represent a risk factor for HCC among HCV-infected patients. The interplay between the two genes may explain some of the controversy on this topic and may be exploited to stratify HCC risk in hepatitis C.